SAT0531 Acute phase reactant levels and prednisone doses at disease flare in patients with giant cell arteritis: prospective data from the giacta trial. (12th June 2018) - Stone, J.H.; Tuckwell, K.; Dimonaco, S.; Klearman, M.; Aringer, M.; Blockmans, D.; Brouwer, E.; Cid, M.C.; Dasgupta, B.; Rech, J.; Salvarani, C.; Schulze-Koops, H.; et al.
Abstract : Background: The relationship between acute phase reactant levels and giant cell arteritis (GCA) disease flares is not known, particularly in the era of interleukin-6 receptor blockade with tocilizumab (TCZ). Prednisone doses at which GCA flares can occur have not been studied thoroughly in prospective clinical trials. Objectives: Investigate prednisone doses and acute phase reactant levels at the time of disease flare in patients with GCA. Methods: Secondary analyses of prednisone doses, C-reactive protein (CRP) levels, and erythrocyte sedimentation rate (ESR) were performed for patients who experienced GCA flare after achieving remission during 52 weeks of treatment with TCZ-weekly or -every-other-week+26 week prednisone taper (TCZ-QW or TCZ-Q2W) or placebo +26 week or 52 week prednisone taper (PBO+26 or PBO+52). The last CRP and ESR values before first disease flare were used if values on the day of first flare were missing. Analyses are descriptive and were performed post hoc. Results: GCA flare after remission was reported in 23% (23/100) of TCZ-QW patients, 26% (13/50) of TCZ-Q2W patients, 68% (34/50) of PBO +26 patients, and 49% (25/51) of PBO +52 patients. 1 Median CRP levels and ESR at the time of flare were lower in the TCZ groups than in the PBO groups (Table). In the TCZ groups, 92% (33/36) of flares were associated with normal CRP levels (≤1 mg/dL) and 89% (32/36) were associated with normal ESR values (<30 mm/h). In the PBO groups, 34% (20/59) of flares were associated with normal CRP values and 31% (18/59) with normal ESR. Median (min–max) prednisone doses at the time of disease flare in the combined TCZ and combined PBO groups were 5.5 (0.0–310.0) and 9.0 (0.0–55.0) mg/day, respectively. Among 149 patients in the TCZ groups, 10 (7%) had disease flares while receiving prednisone doses greater than 10 mg/day, accounting for 28% of all disease flares in the TCZ groups. Among 101 patients in the PBO groups, 23 (23%) had disease flares while receiving prednisone doses>10 mg/day, accounting for 39% of all disease flares in the PBO groups. Thus, 33 of the 95 disease flares in GiACTA (35%) occurred while the patient was receiving ≥10 mg/day prednisone. Conclusions: Acute phase reactants are not reliable correlates of disease flare in TCZ-treated patients, but approximately one-third of all PBO +prednisone patients also had normal acute phase reactants at the time of disease flare. Median prednisone dose at the time of disease flare for TCZ-treated patients was numerically lower than that of patients treated with PBO +prednisone. One-third of all disease flares in GiACTA occurred while the patient was receiving >10 mg/day prednisone. Reference: [1] Stone JH, et al. N Engl J Med2017;377:317–328. Acknowledgements: This study was sponsored by F. Hoffmann-La Roche Ltd. Disclosure of Interest: J. Stone Grant/research support from: Roche, Genentech, Xencor, Consultant for: Roche, Genentech, Xencor, K. Tuckwell Shareholder of: Roche, Employee of: Genentech, S. Dimonaco Employee of: Roche, M. Klearman Employee of: Genentech, M. Aringer Consultant for: Chugai, Roche, Speakers bureau: Chugai, Roche, D. Blockmans: None declared, E. Brouwer Grant/research support from: Roche, M. C. Cid Consultant for: Roche, Novartis, Boehringer-Ingelheim, B. Dasgupta Consultant for: Roche, GlaxoSmithKline, J. Rech: None declared, C. Salvarani: None declared, H. Schulze-Koops: None declared, G. Schett Grant/research support from: AbbVie, BMS, Celgene, Chugai, GSK, Lilly, Novartis, Roche, Sanofi, UCB, Consultant for: AbbVie, BMS, Celgene, Chugai, GSK, Lilly, Novartis, Roche, Sanofi, UCB, R. Spiera Grant/research support from: Roche/Genentech, Consultant for: Roche/Genentech, S. H. Unizony: None declared, N. Collinson Employee of: Roche